Expedient synthesis of an atypical oxazolidinone compound library. Issue 21 (1st November 2016) - Cully, Sarah J.; Storr, Thomas E.; Rawling, Michael J.; Abeysena, Induka R.; Hamza, Daniel; Jones, Geraint; Pearce, Christopher A.; Quddus, Abdul; Lewis, William; Stockman, Robert A.
Graphical abstract: Abstract: In order to address the current downturn in the drug discovery pipeline, initiatives are being undertaken to synthesise screening libraries of sp 3 -rich, low molecular weight compounds. As part of the European Lead Factory initiative, the synthesis and derivatisation of a simple hexahydrooxazolo[5, 4- c ]pyridin-2(1 H )-one bicyclic carbamate has been achieved. The synthetic route employed involved a telescoped hetero-Diels–Alder/[2, 3]-sigmatropic rearrangement/cyclisation sequence to deliver the desired core scaffold containing two points for further diversification. When applied, this synthesis was found to be robust and scalable which allowed the production of a 155 compound library.